1947
DOI: 10.1021/ie50452a015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time and Temperature of Storage on Vitamin Content of Commercially Canned Fruits and Fruit Juices (Stored 12 Months)

Abstract: The effect of 4, 8, and 12 months' storage at 50°, 65°, and 80°F. on the ascorbic acid, carotene, niacin, riboflavin, and thiamine content of seventeen lots of canned fruits and fruit juices has been studied. Comparisons were also made as to the effect of a year's storage, in nine warehouses located in cities throughout the United States, on the ascorbic acid and thiamine content of tomatoes and orange juice. The canned foods, held under constant temperature conditions, at 50°F. showed no significant losses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1948
1948
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Studied. Inasmuch as a comparable investigation of vitamin retention in commercially canned fruits and fruit juices (7) was being planned, it was placed in storage; for the western samples this interval was somewhat longer.…”
Section: Productsmentioning
confidence: 99%
“…Studied. Inasmuch as a comparable investigation of vitamin retention in commercially canned fruits and fruit juices (7) was being planned, it was placed in storage; for the western samples this interval was somewhat longer.…”
Section: Productsmentioning
confidence: 99%
“…Loss of AA in single-strength grapefruit juice (SSGJ) has been shown to be related to storage time and temperature (Moore et al, 1944;Riester et al, 1945;Lamb, 1946;Moschette et al, 1947;Sheft et al, 1949;Moore, 1949;Freed et al, 1949;Heikal et al, 1967). In those studies, however, TAVC was not determined and most of those studies did not cover a wide range of storage temperatures.…”
mentioning
confidence: 99%
“…Temperatures should not only include those of normal storage (15-25 °C) but also those attained during adverse conditions. In a nationwide survey, several researchers (Moschette et al, 1947, Freed et al, 1949 reported that the temperature of non-air-conditioned warehouses ranged from below freezing to over 35 °C. Recent information (Ratcliff, 1978) indicates that warehouse temperatures in Florida range as high as 65 °C.…”
mentioning
confidence: 99%
“…Many studies (Moschette et al, 1947;Sheft et al, 1949;Freed et al, 1949;Blundstone et al, 1971;Bissett and Berry, 1975) have shown loss of vitamin C in singlestrength orange juice (SSOJ) was related to storage temperatures. High-temperature loss of vitamin C may result from processing, unfavorable heat dissipation of the freshly processed juice (stack-burn), warehouse storage (heat pockets, poor air circulation, improper insulation), poor transit conditions (over-heated tractor trailers, railway cars, etc.…”
mentioning
confidence: 99%